MODEL REGRESI COX UNTUK MENGANALISIS PENGARUH FAKTOR ASUPAN MAKANAN TERHADAP RISIKO KEKAMBUHAN ENDOMETRIOSIS - Eliyati, Ning; Maiyanti, Sri Indra; Dwipurwani, Oki; Hamidah, Shaly Wanda (PATTIMURA UNIVERSITY, 2021)
This research purpose is to analyze the relationship between food intake factors (fruit, soy, milk, caffeine, red meat, garlic, ginger, seafood, cheese, green tea, brown rice, wheat, potatoes, bean sprouts, mustard greens, soft drinks and alcohol) on hazard of endometriosis recurrence, using the Cox proportional hazard model backward method. The results of the food intake factors that significantly reduced the risk of endometriosis recurrence are fruit 1-4 times/week (p-value 0.01), fruit 5-7 1-4 times/week (p-value 0.08), mustard greens 1-7 times/week (p-value 0.006), bean sprouts 3-7 (p-value 0.007) and seafood times/week. Factors that increase the risk of endometriosis recurrence are consumption of milk 3-4 times/week (p-value 0.004), seafood 1-2 times (p-value 0.00), soy 1-2 times/week (p-value 0.002), and 3-7 times/week (p-value 0.001). Soy consumption 1-2 and 3-7 times/week are likely to relapse 30.3 and 43.9 times compared to soy consumption <1 times/week. Consumption of milk 3-4 times/week has a risk of relapse 24 times compared to consume milk <1 times/week